Internet Use for Health-Related Information via Personal Computers and Cell Phones in Japan: A Cross-Sectional Population-Based Survey - Takahashi, Yoshimitsu; Ohura, Tomoko; Ishizaki, Tatsuro; Okamoto, Shigeru; Miki, Kenji; Naito, Mariko; Akamatsu, Rie; Sugimori, Hiroki; Yoshiike, Nobuo; Miyaki, Koichi; Shimbo, Takuro; Nakayama, Takeo (JMIR Publications, 2011)
BackgroundThe Internet is known to be used for health purposes by the general public all over the world. However, little is known about the use of, attitudes toward, and activities regarding eHealth among the Japanese population. ObjectivesThis study aimed to measure the prevalence of Internet use for health-related information compared with other sources, and to examine the effects on user knowledge, attitudes, and activities with regard to Internet use for health-related information in Japan. We examined the extent of use via personal computers and cell phones. MethodsWe conducted a cross-sectional survey of a quasi-representative sample (N = 1200) of the Japanese general population aged 15-79 years in September 2007. The main outcome measures were (1) self-reported rates of Internet use in the past year to acquire health-related information and to contact health professionals, family, friends, and peers specifically for health-related purposes, and (2) perceived effects of Internet use on health care. ResultsThe prevalence of Internet use via personal computer for acquiring health-related information was 23.8% (286/1200) among those surveyed, whereas the prevalence via cell phone was 6% (77). Internet use via both personal computer and cell phone for communicating with health professionals, family, friends, or peers was not common. The Internet was used via personal computer for acquiring health-related information primarily by younger people, people with higher education levels, and people with higher household incomes. The majority of those who used the Internet for health care purposes responded that the Internet improved their knowledge or affected their lifestyle attitude, and that they felt confident in the health-related information they obtained from the Internet. However, less than one-quarter thought it improved their ability to manage their health or affected their health-related activities. ConclusionsJapanese moderately used the Internet via personal computers for health purposes, and rarely used the Internet via cell phones. Older people, people with lower education levels, and people with lower household incomes were less likely to access the Internet via cell phone. The Internet moderately improved users' health-related knowledge and attitudes but seldom changed their health-related abilities and activities. To encourage communication between health providers and consumers, it is important to improve eHealth literacy, especially in middle-aged people. It is also important to make adequate amendments to the reimbursement payment system and nationwide eHealth privacy and security framework, and to develop a collaborative relationship among industry, government, and academia.